AB0098 The Beneficial Role of PAI-1 in Bone-Cartilage Interaction. (9th June 2015) - Pustjens, M.F.; Mastbergen, S.C.; Noort-van der Laan, W.H.; van Heerwaarden, R.J.; Lafeber, F.P.
Abstract : Background: In osteoarthritis (OA) subchondral bone changes are seen in addition to cartilage changes. In treatments targeted at bone, such as treatment with strontium ranelate [1], or treatments with bone involvement such as osteotomy [2] or joint distraction [3], cartilage repair has been demonstrated. These studies support the hypothesis that changes in bone metabolism can lead to cartilage repair. However, the exact biochemical interactions and how they contribute to repair and degradation processes is less well known. Plasminogen activator inhibitor (PAI)-1 inhibits plasmin which causes higher levels of MMPs in OA. It is expressed in subchondral bone and cartilage. Objectives: The present study evaluates the role of PAI-1 in bone-cartilage interaction and its direct effects on osteoarthritic cartilage. Methods: Both healthy and OA cartilage was cultured with supernatant from healthy (n=14) and OA (n=16) donors and proteoglycan (PG) synthesis was studied. Expression levels of mediators were assessed in the osteoblast culture supernatants by Luminex analysis. Subsequently, OA cartilage (n=11 donors) was cultured in absence/presence of PAI-1 and PG synthesis changes were studied. Results: PG synthesis of OA cartilage was increased (+34%, p=0.036) upon addition of healthy osteoblast supernatant. Importantly, a decrease was seen when OA osteoblast supernatant was added to healthy cartilage (-31% PG synthesis, p=0.001). PAI-1 was expressed at significant higher levels in healthy osteoblasts compared to OA osteoblasts (184ng/ml vs 91ng/ml, resp.p=0.015). Moreover, osteoblast PAI-1 levels were positively correlated with PG synthesis (r=0.595, p=0.042) influenced by the osteoblasts. Culturing OA cartilage in direct presence of PAI-1 (2000ng/ml) revealed 33% (p=0.026) increase of PG synthesis confirming the beneficial role of PAI-1 in the osteoblast cultures. Conclusions: Healthy osteoblast derived mediators lead to PG synthesis increase in OA cartilage, while it has no effect on healthy cartilage. Moreover, OA osteoblast derived mediators lead to a decrease in PG synthesis in healthy cartilage, but not in OA cartilage. Higher PAI-1 levels in these osteoblasts cultures are clearly correlated with higher PG synthesis in cartilage, which hints at a role for PAI-1 in cartilage repair. Its direct effects on OA cartilage, increasing PG synthesis, further confirmed the relevance of PAI-1. This supports that targeting bone directly or involvement of bone might be feasible as treatment for OA. References: Reginster JY, Beaudart C, Neuprez A, Bruyère O (2013) Ther Adv Musculoskelet Dis. 5(5): 268-76. Jung WH, Takeuchi R, Chun CW, Lee JS, Ha JH, Kim JH, Jeong JH (2014) Arthroscopy 30(1):72-9. Intema F, Van Roermund PM, Marijnissen AC, Cotofana S, Eckstein F, Castelein RM, Bijlsma JW, Mastbergen SC, Lafeber FP (2011) Ann Rheum Dis.:70(8):1441-6. Acknowledgements: This study was funded by the Dutch Arthritis Association. Disclosure of Interest: None declared